Survival strategies in contexts of socio-environmental vulnerability among small-scale farmers in semiarid areas of northeastern Mexico - Navarro Hinojoza, Ernesto (2023)
Despite their vulnerabilities, rural populations of the Coahuila semi-desert area persist with the hope of subsisting. The objective of the paper was to analyze the life strategies of small-scale farmers and the influence of these strategies on the perceived well-being of the household. The study area was Ejido Chapultepec, in Arteaga, Coahuila. The methodology used was an adaptation of the Sustainable Livelihoods Approach. A total of 29 semi-structured interviews were conducted with key informants during 2020 through a proven volunteer-directed approach to the point of saturation, in addition to walkthroughs and field observation. A characterization and typification of the producers as well as an analysis of vulnerabilities were generated. As life strategies, they all conduct multiple activities, temporary migration, and work in the industry. The agricultural activity is part-time. Due to changes in rainfall patterns, they have had to change crops, planting dates, or even abandon activities. They all report feeling satisfied and well. It is concluded that the livelihoods of the studied population are predominantly based on pluriactivity, under contexts of ecosocial vulnerability leading them to significant changes in their life strategies.